Food texture and sweetener type modify sweetness perception in whey protein‐based model foods. Issue 4 (9th May 2018) - Wagoner, T. B.; McCain, H. R.; Foegeding, E. A.; Drake, M. A.
Abstract: In an effort to formulate healthier food products, sugar is often reduced or replaced with artificial or natural non‐nutritive sweeteners. However, the removal of sucrose often changes food texture, and non‐nutritive sweeteners inherently exhibit differences in sweetness quality, onset, and overall intensity. Therefore, the objectives of this study were to evaluate the effects of texture on sweetness dose‐response profiles of whey protein solutions sweetened with sucrose, sucralose, stevia, or monk fruit extracts, and to assess temporal progression of dominant attributes. Whey protein‐based model foods with different textural properties were generated without modifying composition by varying heating time. Dose‐response power functions and iso‐sweet equivalencies were determined using magnitude estimation scaling. Temporal profiles of dominant texture, taste, and flavor attributes were evaluated using temporal dominance of sensations (TDS). A significant texture‐sweetener interaction effect was observed ( p  < .05), where more viscous or semisolid textures required greater amounts of sweetener for iso‐sweetness. Moreover, the dose‐response slope decreased with increasing thickness for sucralose, stevia, and monk fruit‐sweetened textures. Results of TDS indicated that increased thickness prolonged the dominance of several attributes. This study shows that sugar reduction strategies are not universal; food matrix, sweetener type, and usage level need to be considered when attempting to modify texture or reduce sucrose. Practical applications: Sucrose reduction, use of nonnutritive sweeteners, and texture modification are all ways in which food manufacturers can increase the healthful quality of the food supply. However, these types of modifications can alter the overall sensory properties of a food. Texture‐taste interactions are not currently well understood, and knowledge in this area is important for designing ways to modify texture or reduce sucrose for health and enjoyment. The results of this study provide insight into texture‐taste interactions, indicating that sugar reduction or replacement strategies are not one size fits all and are likely product and sweetener‐specific.